Exporting Transnational Education Institutional Practice, Policy and National Goals (Springer International Publishing, 2018)
This book focuses on the dynamic and rapidly expanding field of transnational higher education (TNE). Despite the increasing importance of TNE and the interest it has attracted from various stakeholders, there is a lack of theoretical and empirical evidence on several aspects pertaining to its operation and governance. This book provides a unique combination of contributions from researchers and practitioners in a wide variety of case studies from TNE exporting countries in Europe and Asia. In doing so, the editors, with added support from Dr Christopher Hill, examine how this gap between research and practice can be bridged. This valuable edited collection will be of use to researchers and practitioners in transnational education, as well as students and scholars of international education and higher education policy.